If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(3x+4)-2x=-2x-3(-2x+11)-1
We move all terms to the left:
5(3x+4)-2x-(-2x-3(-2x+11)-1)=0
We add all the numbers together, and all the variables
-2x+5(3x+4)-(-2x-3(-2x+11)-1)=0
We multiply parentheses
-2x+15x-(-2x-3(-2x+11)-1)+20=0
We calculate terms in parentheses: -(-2x-3(-2x+11)-1), so:We add all the numbers together, and all the variables
-2x-3(-2x+11)-1
We multiply parentheses
-2x+6x-33-1
We add all the numbers together, and all the variables
4x-34
Back to the equation:
-(4x-34)
13x-(4x-34)+20=0
We get rid of parentheses
13x-4x+34+20=0
We add all the numbers together, and all the variables
9x+54=0
We move all terms containing x to the left, all other terms to the right
9x=-54
x=-54/9
x=-6
| -42t+8=20 | | 21=3b+4b | | 20=5-6x | | 3b=18. | | 3x3+3÷3-3=x | | 78=q/7+72 | | 17x-9=10x+3 | | 3x+14=7x-4) | | 17Xv=323 | | 0.5d-6=5 | | 2x-3+8=-4x | | (180-26x+6)+7x+2+80=180 | | f(5)=3(5)-10 | | a4=102 | | -6.5x=2-(9x-1) | | 35-x=17-5 | | 1/8k-2=3/8k+4 | | z/3-9=3 | | -x+9-12x=-160 | | 549.94-49.99x=299.99 | | 10x+10=19x-4=180 | | 55=7+12x | | 3(–4z+7)=–39 | | 15n=-150 | | 33=4s-7 | | -6w+32=2 | | 3x-29=2x=15 | | -4(-6v+4)-9v=3(v-9)-4 | | 9(+1)=2(n-1) | | x-20=32-14 | | 6(2+3m)=4(6+3m) | | -3(2g-6)=54 |